2012
DOI: 10.1111/j.1442-2050.2012.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with a reduction in the incidence of esophageal adenocarcinoma: a case control study

Abstract: The incidence of esophageal adenocarcinoma (EAC) is increasing significantly throughout the developed world. As yet, there are no proven chemopreventive strategies. In laboratory studies, aspirin, non-steroidal anti-inflammatory drugs and statins have promising chemopreventive actions. Several observational studies support a protective effect of aspirin and non-steroidal anti-inflammatory drugs, but there are only limited clinical data exploring the potential protective effect of statins. We conducted a case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The main strengths of our study are the accurate and full records of medication exposure as reported previously (14,15,23) and the ability to correlate this with clearly defined endoscopic findings within the context of an adequately powered study. The main weakness, inherent in any observational study, is that of uncorrected bias.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main strengths of our study are the accurate and full records of medication exposure as reported previously (14,15,23) and the ability to correlate this with clearly defined endoscopic findings within the context of an adequately powered study. The main weakness, inherent in any observational study, is that of uncorrected bias.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the groups were quantified using the calculated odds ratios and 95% confidence intervals, with the significance level set at P < 0.05. Unconditional logistic regression was used to correct for potentially confounding 8 factors: age, smoking, alcohol use, body mass index, waist circumference and all prescribed and over the counter mediations recorded (14,15,19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations